Ionome and elemental transport kinetics shaped by parallel evolution in threespine stickleback. (5th February 2019) - Rudman, Seth M.; Goos, Jared M.; Burant, Joseph B.; Brix, Kevin V.; Gibbons, Taylor C.; Brauner, Colin J.; Jeyasingh, Punidan D.
Abstract: Evidence that organisms evolve rapidly enough to alter ecological dynamics necessitates investigation of the reciprocal links between ecology and evolution. Data that link genotype to phenotype to ecology are needed to understand both the process and ecological consequences of rapid evolution. Here, we quantified the suite of elements in individuals (i.e., ionome) and differences in the fluxes of key nutrients across populations of threespine stickleback. We find that allelic variation associated with freshwater adaptation that controls bony plating is associated with changes in the ionome and nutrient recycling. More broadly, we find that adaptation of marine stickleback to freshwater conditions shifts the ionomes of natural populations and populations raised in common gardens. In both cases ionomic divergence between populations was primarily driven by differences in trace elements rather than elements typically associated with bone. These findings demonstrate the utility of ecological stoichiometry and the importance of ionome‐wide data in understanding eco‐evolutionary dynamics.